2020
DOI: 10.1111/ejn.14914
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric distribution of pallial‐expressed genes in zebrafish (Danio rerio)

Abstract: The left and right distribution of a set of twenty‐six genes in the zebrafish pallium was examined by RT‐qPCR experiments. The analysis comprised four general pallial markers (eomesa, emx2, emx3 and prox1); eight genes, dapper1, htr3a, htr3b, htr4, id2, ndr2, pkcβ and lmo4, that have been described as asymmetric distributed in the brain of mammals (human and mouse); six genes, arrb2, auts2, baiap2, fez1, gap43 and robo1, asymmetrically distributed in the mammalian cortex, that have been associated with autism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 82 publications
(149 reference statements)
7
20
4
Order By: Relevance
“…Further studies will be necessary to investigate the impact of VPA on neurodevelopmental mechanisms relevant to ASD pathogenesis. Several studies have indicated that VPA affects genes asymmetrically expressed in the brain of many vertebrate species ( 5htr3a, 5htr3b and 5htr4 ) [ 21 , 28 , 29 ], including zebrafish, suggesting a potential role of this substance in the alteration of brain asymmetry associated with ASDs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies will be necessary to investigate the impact of VPA on neurodevelopmental mechanisms relevant to ASD pathogenesis. Several studies have indicated that VPA affects genes asymmetrically expressed in the brain of many vertebrate species ( 5htr3a, 5htr3b and 5htr4 ) [ 21 , 28 , 29 ], including zebrafish, suggesting a potential role of this substance in the alteration of brain asymmetry associated with ASDs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The triplicate reactions/samples were performed using the PowerUp™ SYBR™ Green Master Mix (2×) and a CFX96™ Real-Time System (Bio-Rad, Milan, Italy). The DCT method was used for expression quantification [ 21 ]. Data were normalized on the expression of the 18S reference gene.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, there was no detectable difference in the expression of these three genes, which could be explained by the lack of such vocal communication in zebrafish. Nonetheless, the expression pattern of both robo1 and foxp2 becomes neuroanatomically and functionally more complex during zebrafish adulthood (38, 39). Thus, Baz1b could still be influencing their expression in zebrafish but at later stages to the ones studied here.…”
Section: Discussionmentioning
confidence: 99%
“…As to the former, the possibility of elucidating the development and the neural connectivity of magnitude/number neurons in wild-type, knock-in and knock-out transgenic lines, as well as the possibility to trace the biological evolution of number sense in vertebrates. As to the latter, research on zebrafish would promise a better understanding and modelling of developmental dyscalculia [ 156 , 157 ].…”
Section: Implications Of Neurobiological Research Of Number Cognition In Zebrafishmentioning
confidence: 99%
“…In the last few years, zebrafish became a valid alternative to mouse to model human pathologies [ 157 , 158 , 159 ] since this fish is easier to genetically manipulate (for example using CRISPR/Cas9 genome editing), to imagine in vivo (because of larval transparency), and to test in large groups of individuals in order to analyze all stage of development in a very short time (from few hours to adulthood). A first screening of gene expression analyses of nine genes (baz1b, fzd9, limk1, tubgcp5, cyfip1, grik1a, robo1, nipa1 and nipa2) associated with human developmental dyscalculia [ 160 , 161 , 162 , 163 ] revealed a large expression of all of them in the zebrafish adult pallium and, for five genes (grik1a, robo1, nipa1 and nipa2) an asymmetric distribution between the right and left hemispheres ([ 157 ]; see for a general review on brain asymmetry [ 164 ] and in fish [ 165 ]). The asymmetric distribution of some of the genes associated with human dyscalculia opens the way to the crucial theme that links laterality with number sense and its pathologies [ 166 , 167 ].…”
Section: Implications Of Neurobiological Research Of Number Cognition In Zebrafishmentioning
confidence: 99%